Dyscyplina naukowa i tożsamość naukowca - Melosik, Zbyszko (Studia Edukacyjne, 2019)
The article is devoted to analysis of the relationships between the identity of scholar and her/his research discipline. The historical, cognitive and social contexts of disciplines is considered against the background of the university scholar identification. Besides the following issues are dicussed in the article: institutionalization of the discipline, the role of epistemic communities, changing borders of discipline, multidisciplinary approach to research, language of disciplines, status of disciplines and the meaning of academic freedom.